ANALISIS PERUBAHAN NILAI SUCTION AKIBAT HUJAN TERHADAP KESTABILAN LERENG - Martini Martini (MEKTEK, 2012)
Infiltration of rainfall into slope will have an effect on to condition of slope hydrology and more specifically to characteristic of slope soils, for example pore water pressure value, level of saturation, weight contents of soil, shear strength of soil. Pore water pressure value at dry soil condition or wet condition called as with pore water pressure value negatife or value suction. This suction value will tend to declines and in the end becomes equal to zero or bigger than 0 ( positive pore water pressure) in the event of change of the water content from condition unsaturated to saturated condition. Speed of value change suction becomes positive pore water pressure most influenced by rain intensity. Value suction which is quickest fastest changed at slope at foot of slope